Pengaruh Kualitas Produk, Harga, Dan Merek Program Khusus Terhadap Minat Konsumen Pada SD Muhammadiyah Program Khusus Kota Barat Surakarta - Yulianto, Didik Adi, Ahmad Mardalis, S.E.,MBA (2016)
This study aims to determine the effect of product quality , price , and brand "special program" on consumer interest in SD Muhammadiyah Surakarta "special programs" West Town . This research is quantitative . The population in this study is the Parents Guardians SD Muhammadiyah Surakarta West City "special program" totaling 380 respondents. The sample in this study is 158. The data analysis used in this study were using multiple linear regression analysis. The result of this research is Quality Products (X1) has no effect on Consumer Interests (Y). Price (X2) has no effect on Consumer Interests (Y). Brand (X3) influence on Consumer Interests (Y). Testing the overall hypothesis of F test hypotheses prove influential and significant impact on consumer interests together. The results also showed that brand influence is greater than any other variable, and therefore to increase the interest of parents to enroll school administrators need to improve service processes. Keywords : Product Quality , Price , Brand , Consumer Interests